2020
DOI: 10.1075/lab.19037.liu
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilinguals who do not speak a tone language show enhancement in pitch sensitivity but not in executive function

Abstract: This study examines the influence of listeners’ language experience on their pitch processing in language and music, cognitive abilities and potential interactions across these domains and modalities. Twenty-four Dutch, 24 Dutch simultaneous bilingual (DSB) and 24 Mandarin listeners were tested on three sets of tasks assessing their linguistic pitch, music perception and executive function. Both DSB and Chinese listeners outperformed their Dutch peers in linguistic pitch perception and pitch-related music task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Similar observations were made from the correlation analyses, where tone discrimination accuracy was positively correlated with years of musical training as well as musical aptitude (as measured by the MET) among the single-tone language speakers, but not dual-tone language speakers. Our findings echo observations in previous studies that among non-tone language speakers but not among tone language speakers, tone processing is enhanced by musical training ( Cooper and Wang, 2012 ; Mok and Zuo, 2012 ; Maggu et al, 2018a ; Chen et al, 2020 ; Laméris and Post, 2022 ) or musical aptitude ( Chen et al, 2016 ; Liu et al, 2020 ). Our findings further suggest that even among tone language speakers, individuals with less tone language experience benefit more greatly from musical experience for tone perception compared to individuals with additional tone language experience.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar observations were made from the correlation analyses, where tone discrimination accuracy was positively correlated with years of musical training as well as musical aptitude (as measured by the MET) among the single-tone language speakers, but not dual-tone language speakers. Our findings echo observations in previous studies that among non-tone language speakers but not among tone language speakers, tone processing is enhanced by musical training ( Cooper and Wang, 2012 ; Mok and Zuo, 2012 ; Maggu et al, 2018a ; Chen et al, 2020 ; Laméris and Post, 2022 ) or musical aptitude ( Chen et al, 2016 ; Liu et al, 2020 ). Our findings further suggest that even among tone language speakers, individuals with less tone language experience benefit more greatly from musical experience for tone perception compared to individuals with additional tone language experience.…”
Section: Discussionsupporting
confidence: 90%
“… Wiener and Goss (2019) also found that speakers of L1 Mandarin Chinese (and L2 English) and L3 Japanese, which is a pitch accent language, outperform speakers of L1 Japanese (and L2 English) in a Japanese pitch accent discrimination task. Notably, this effect cannot be attributed to a general bilingual advantage in cognitive functions per se , as several studies have found no significant differences between speakers of two non-tone languages and speakers of one non-tone language in a tone discrimination task ( Liu et al, 2020 ) and tone word learning task ( Blumenfeld and Adams, 2014 ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a result, our estimates of the effect of musical training have greater uncertainty (although the analyses for participants with no musical training, which largely replicate the main effects, help to mitigate this concern). Second, participants only reported their first language, so we were unable to examine the effects of bilingualism or multilingualism (Krizman et al, 2012; Liu et al, 2020; Liu & Kager, 2017), nor assess whether fluently speaking both tonal and non-tonal languages (e.g. Mandarin and English) might have contributed additional variability in our results.…”
Section: Discussionmentioning
confidence: 99%